Out of Africa: a molecular perspective on the introduction of yellow fever virus into the Americas. - Juliet E Bryant; Edward C Holmes; Alan D T Barrett (PLoS Pathogens)
Yellow fever virus (YFV) remains the cause of severe morbidity and mortality in South America and Africa. To determine the evolutionary history of this important reemerging pathogen, we performed a phylogenetic analysis of the largest YFV data set compiled to date, representing the prM/E gene region from 133 viral isolates sampled from 22 countries over a period of 76 years. We estimate that the currently circulating strains of YFV arose in Africa within the last 1,500 years and emerged in the Americas following the slave trade approximately 300-400 years ago. These viruses then spread westwards across the continent and persist there to this day in the jungles of South America. We therefore illustrate how gene sequence data can be used to test hypotheses of viral dispersal and demographics, and document the role of human migration in the spread of infectious disease.